2016
DOI: 10.7181/acfs.2016.17.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Analysis of Facial Foramina in Korean Population: A Three-Dimensional Computed Tomographic Study

Abstract: BackgroundPosition of the facial foramina is important for regional block and for various maxillofacial surgical procedures. In this study, we report on anthropometry and morphology of these foramina using three-dimensional computed tomography (3D-CT) data.MethodsA retrospective review was performed for all patients who have undergone 3D-CT scan of the facial skeleton for reasons other than fracture or deformity of the facial skeleton. Anthropometry of the supraorbital, infraorbital, and mental foramina (SOF, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…The infraorbital foramen (IOF) is present on the maxillary bone. The infraorbital nerve, vein, and artery pass through this foramen [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The infraorbital foramen (IOF) is present on the maxillary bone. The infraorbital nerve, vein, and artery pass through this foramen [1].…”
Section: Introductionmentioning
confidence: 99%
“…The infraorbital nerve is an essential facial sensory nerve. It originates from the trigeminal ganglion, passes through the facial skeleton, and exits through the infraorbital foramen [1]. It is responsible for sensation in the upper cheek, the inferior eyelid, part of the nose, the upper lip, the maxillary sinus, and some of the maxillary teeth [2].…”
Section: Introductionmentioning
confidence: 99%
“…43 Among Korean population MF is coincided most commonly with the lower 2 nd premolar. 44 According to another study, the most commonly found appearance of MF was the continuous type with respect to the mandibular canal. The most frequent superior-inferior position is, below the level of the apices of the premolar.…”
Section: Discussionmentioning
confidence: 97%
“…The current literature suggests there is sufficient variability between previous publications to warrant a thorough investigation of the SONF, IOF, and MF (Agthong et al, 2005). Even more importantly, there is evidence to suggest there are ethnic variations in the location of the facial foramina (Agthong et al, 2005; Chung et al, 1995; Gupta, 2008; Lim et al, 2016; Zhang et al,l.,l.,l., 2019). Previous reports suggest that race and ethnicity may influence the position of the SONF, IOF, and MF; thus, the current surgical guideline may be specific to certain races and ethnicities.…”
Section: Introductionmentioning
confidence: 99%
“…A study of dried skulls of a North‐West Indian population stated that in 80% of the skulls the SONF, IOF, and MF were on the same vertical plane (Gupta, 2008). However, studies analyzing these same foramina in Korean and Sri Lankan populations found that for a majority of subjects studied each foramen was not equidistant from the median plane (Agthong et al, 2005; Chung et al, 1995; Gupta, 2008; Lim et al, 2016). It should be noted that only 38.1% of the Korean sample and 7% of the Sri Lankan sample had SONF, IOF, and MF equidistant from the midline (Chung et al, 1995; Nanayakkara et al, 2016).…”
Section: Introductionmentioning
confidence: 99%